Experiments in plant tissue culture - Dodds, John H. (Cambridge University Press, 1995)
In this third edition the authors have written a guide to the essentials of plant tissue culture. The book takes the reader through a graded series of experimental protocols and provides an introductory review of each topic. There are discussions of aseptic techniques, and nutritional components of media. Subsequent chapters cover such topics as callus formation, organogenesis, xylem cell differentiation, root cultures, cell suspensions, micropropagation by buds, somatic embryogenesis, protoplast culture and fusion, secondary metabolite production, and quantitation of procedures, amongst others. A glossary, commercial sources of supplies, and the formulations of culture media are also included. This new edition has been completely revised and updated. The organization has been improved, and new illustrations added, together with new experiments on such topics as potato callus formation, and embryo culture.